If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + -9) = -33 Reorder the terms: 3(-9 + x) = -33 (-9 * 3 + x * 3) = -33 (-27 + 3x) = -33 Solving -27 + 3x = -33 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '27' to each side of the equation. -27 + 27 + 3x = -33 + 27 Combine like terms: -27 + 27 = 0 0 + 3x = -33 + 27 3x = -33 + 27 Combine like terms: -33 + 27 = -6 3x = -6 Divide each side by '3'. x = -2 Simplifying x = -2
| 7x+40=5x-10 | | 1/(x^2-1)= | | 1.7/x=0.15/150 | | x+2x+(2x+7)= | | x^4-3x^2-36=0 | | 6x+6=5x-2 | | 5x+6=5x-2 | | 8(x+3)-2(x-3)=2(x-3)+3(x-3) | | 6x+12=-72 | | 15/6=6x/6 | | -10-8t=.3t | | k^2=-16-10k | | X+4y=o | | y=16x+2 | | x^6=1.97 | | y=-5E-06x+4.87 | | 7.5/6=6x/6 | | 16x+74=33 | | 1+log(x)=0 | | 60/6=6x/6 | | (6-2i)/(1-3i) | | (3y-6)(y-6)=420 | | 3y-6*y-6=420 | | Z/2×x=z^2/6 | | sin(8x)=sin(x) | | 1x+1=-12 | | X/0.03= | | 4x^2(x+3)+4x=-15(x+1) | | X/0.2=0.7 | | 9y+10=64 | | 7=k/9 | | 11z+5=82 |